GLOBAL DIGITALIZATION: PATHS AND PROBLEMS - Bustonov, Mansurjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
During the twentieth century, one of the most striking global shifts was the integration of the Internet into virtually every dimension of human activity. The acceleration of economic and entrepreneurial practices under the pressure of fast-evolving online technologies has reshaped traditional patterns and given rise to what is now recognized as the digital economy. Within this framework, innovative digital tools serve as key drivers for unlocking new potentials: enhancing efficiency of business processes, reducing operational expenditures, creating alternative channels for capital mobilization, and expanding opportunities for the advancement of entrepreneurial initiatives. Enhancing the performance of the digital economy through the application of advanced science and technology, stimulating consumer demand for goods and services, and ensuring the delivery of high-quality products by integrating modern equipment and technologies into production processes have become the central priorities of the global economic agenda. At present, the contribution of the digital economy to the gross domestic product differs markedly across countries: it constitutes 5.5% in developed economies and 4.9% in developing ones. More specific figures demonstrate considerable variation — 12.4% in the United Kingdom, 8% in South Korea, 6.9% in China, 5.6% in India, 2.8% in Russia, and 3.9% in Kazakhstan [1].